2022
DOI: 10.1530/etj-21-0124
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of next-generation sequencing and genetic profiling in thyroid nodules from a single center in China

Abstract: Objective: The data regarding the mutation landscape in Chinese patients with thyroid cancer are limited. The diagnostic performance of thyroid nodules by fine-needle aspiration (FNA) cytology needs optimization, especially in indeterminate nodules. Methods: A total of 1039 FNA and surgical resection samples tested using the targeted multigene NGS panel were retrospectively collected. The features of gene alterations in different thyroid tumors were analyzed, and the diagnostic efficacy were evaluated. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Furthermore, we also observed that RET fusion is the independent predictor for LNM, but not the missense mutation. Another clinical study from east China reported 10.4% RET fusions in 193 PTC patients, 31 7.08% RET fusion reported in a study from 14 tertiary hospitals of China 32 . Ullmann et al 33 also reported that RET‐driven tumors are more likely to have extrathyroidal extension, multifocal disease and distant metastases in American.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we also observed that RET fusion is the independent predictor for LNM, but not the missense mutation. Another clinical study from east China reported 10.4% RET fusions in 193 PTC patients, 31 7.08% RET fusion reported in a study from 14 tertiary hospitals of China 32 . Ullmann et al 33 also reported that RET‐driven tumors are more likely to have extrathyroidal extension, multifocal disease and distant metastases in American.…”
Section: Discussionmentioning
confidence: 97%
“…The BRAF V 600E and mutated RAS were considered to be two mutually exclusive drivers of PTC, possibly suggesting similar or redundant downstream effects, and causing different signaling effects followed by profound phenotypic differences ( Cancer Genome Atlas Research, 2014 ; Ren et al, 2022 ) However, less attention had been paid to concurrent molecular alterations, conveying a significant adverse prognosis and suggesting treatment via a total thyroidectomy of the thyroid nodules ( Bose, Sacks & Walts, 2019 ; Ren et al, 2022 ; Poller & Glaysher, 2017 ). In our study, some drivers in the PI3K pathway and tumor suppressor genes manifested a tendency to be concurrent with others, such as BRAF rearrangements and deletions, PTEN deletions, TERT Q302R , and mutations of AKT1 , EIF1AX , TP53, and PIK3CA.…”
Section: Discussionmentioning
confidence: 99%
“…These may result in repeat FNA, diagnostic lobectomy, and even unnecessary total thyroidectomy procedures. Thus, molecular pathogenesis has become a promising approach to supplement cytologic examination for preoperative diagnosis and treatment options ( Ren et al, 2022 ; Lee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a thyroid cancer 18-gene detection kit was independently developed by us and is based on the method of multiplex amplification combined with high-throughput sequencing to detect single nucleotide variants (SNVs), insertions/deletions (Indels), and fusion genes in DNA and RNA. The product was confirmed by internal performance and can achieve 99.3% (SNVs/indels) and 100% (fusion genes) detection accuracy ( 25 ). Under the input of a 5-ng library construction, the limit of detection (LoD) of (DNA) BRAF p.V600E was variant allele frequency (VAF)-1.0%, the LoD of TERT C228T was VAF-2.0%, and the LoD of (RNA) CCDC6 (E1)-RET(E12) fusion detection was 20 ng at a concentration of 20 copies/ng.…”
Section: Introductionmentioning
confidence: 86%